The Use of Filtered Back projection Algorithm for Reconstruction of tomographic Image - Al Hussani, Marwa. T.; Al Hayani, Mohammed H. Ali (Nahrain University College of Engineering Journal, 2014)
Filtered back projection algorithm (FBP) is one of the most common methods that used in to mographic image reconstruction. This algorithm was applied on computerized tomography (CT) scanner. This paper presents the implementation of reconstruction algorithm of CT image 512 x 512 pixels from raw data for the parallel beam projections. This work consist three main parts.In first part, many numbers of projections are obtained from the input test image called Shepp Logan phantom using the Radon transform. The second part, reconstruct the image from parallel beam projection to reduces the reconstruction time. In the third part, filter the projections using Ram Lak filter and Hann window for image enhancement and then back projection summation to form the reconstructed image.The computer program has been designed, written and implemented in our work using MATLAB. This made the result very good for reconstruction two dimensions image from its projection in computerized Tomography scanner.The algorithm was applied on the head phantom image for the purpose of performance improvement.It’s important to many applications like medical and industrial application.